LEVEL OF PHYSICAL ACTIVITY AMONG THE STUDENTS AT THE FACULTY OF MEDICINE WITHIN SS. CYRIL AND METHODIUS UNIVERSITY IN SKOPJE - Trajanov, Darijan; Kjosevska, Elena; Zafirova, Beti Ivanova (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
Physical activity reduces the risk of hypertension, cardiovascular diseases, diabetes and onset of depression. Proper and regular physical activity contributes to balancing body weight. The objective of the paper is to ascertain the level of physical activity among the students at the Faculty of Medicine within Ss. Cyril and Methodius University in Skopje. This research represents a descriptive-analytical study. A total of 316 students in the second and third year of studies at the Faculty of Medicine, Major General Medicine within Ss. Cyril and Methodius University in Skopje participated in the research. In the course of one day, the duration of a moderately intense activity practiced by the students is less than 10 minutes and it amounts to 35.4%, i.e. is evident in 112 students. In the course of one week, students are engaged 2 days in some vigorously intense sports, fitness or recreational activity, i.e. 15.8% (50 students). In the course of one day, the duration of a vigorously intense activity practiced by students is less than 10 minutes and it amounts to 44.3%, i.e. is evident in 140 students. The students are insufficiently physically active, i.e. the students do not observe the recommendations of the World Health Organization that stipulate that the practice of a moderately intense physical activity is to be at least 150 minutes per week, i.e. 75 minutes of a high intensity physical activity or an equivalent combination of a moderate and vigorous physical activity. Key words : physical activity, medical students, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje